First-line systemic treatment adherence, healthcare resource utilization, and costs in patients with gastrointestinal neuroendocrine tumors (GI NETs) in the USA. (3rd August 2018) - Broder, Michael S.; Cai, Beilei; Chang, Eunice; Yan, Tingjian; Benson, Al B.
Abstract: Aims: To assess treatment adherence, healthcare resource utilization, and costs in gastrointestinal neuroendocrine tumor (GI NET) patients initiating pharmacologic treatments in the US. Methods: In two US commercial claims databases, patients ≥18 years with ≥1 inpatient or ≥2 outpatient GI NET claims within 12 months were identified. The first claim for pharmacologic treatments (e.g. somatostatin analogs [SSAs], cytotoxic chemotherapy [CC], targeted therapy [TT]) following diagnosis, between July 1, 2009 – December 31, 2014, was defined as the index date. A 6-month pre-index NET treatment-free period, and ≥1-year post-index enrollment were required. Proportion of days covered (PDC) was calculated during the follow-up period. Outcomes were reported separately for patients with 1- and 2-years post-index enrollment. Descriptive statistics, including means, standard deviations, and frequencies and percentages for continuous and categorical data, respectively, were reported. Results: Of 1, 322 patients with 1-year follow-up, 847 initiated SSA, 397 CC, 35 TT, two interferon, and 41 various combinations. Mean (SD) PDC was 0.669 (0.331) for SSA, 0.466 (0.236) for CC, and 0.505 (0.328) for TT. Mean (SD) office visits and hospitalizations, respectively, were 20.5 (13.5) and 0.59 (1.03) for SSA, 30.5 (19.8) and 0.89 (1.45) for CC, and 17.7 (12.5) and 1.23 (1.93) for TT. Total annual cost for patients during year 1 was $99, 691 (82, 423) for SSA, $134, 912 (116, 078) for CC, and $158, 397 (82, 878) for TT. Among 685 patients with 2-years follow-up, annual mean costs in year 2 were $8, 071, $58, 944, and $36, 248 lower than year 1 for SSA, CC, and TT, respectively. Limitations: Findings may not be generalizable to the US population. Claims are designed for reimbursement, not research. The study may under-estimate costs not covered by insurance. Conclusion: This study reports utilization and costs associated with different treatment therapies. Costs were higher in year 1 than year 2. This two-database study offers new information on the magnitude and trends in the cost of pharmacologically-treated GI NETs.